The art of critical decision making - Roberto, Michael A; Teaching Company (Chantilly, VA : Teaching Co., 2009)
The ability to make wise, educated decisions is essential to living a successful and fulfilled life. Whether simple or complex, private or public, decisions are an essential part of life, affecting individual lives for good or ill, as well as friends, families, and communities. Decision-making is a skill--one that can be learned, honed, and perfected. When the necessary components of a smart decision are understood, mistakes can be sidestepped. When the underlying psychological, social, and emotional components that influence decision-making are known--sounder choices that produce better results can be made. This course explores how individuals, groups, and organizations make effective decisions and offers tips and techniques to enhance effective decision-making.
Lecturer: Michael A. Roberto, Trustee Professor of Management at Bryant University in Smithfield, Rhode Island.
Keywords: Decision making; Critical thinking; Group decision making; Problem solving; Reasoning